Acetylcholinesterase inhibition and micronucleus frequency in oysters (Crassostrea corteziensis) exposed to chlorpyrifos - A B Benitez-Trinidad; Y Y Bernal-Hernández; C L Moreno-Hernández; I M Medina-Díaz; M L Robledo-Marenco; B S Barrón-Vivanco; D Domínguez-Ojeda; C A Romero-Bañuelos; M I Girón-Pérez; A E Rojas-García (Invertebrate Survival Journal, 2014)
Chlorpyrifos (CPF) is an Organophosphorous pesticide (OP) that has been widely used for both agricultural and domestic pest control. To date, there is little information regarding the effects of this pesticide on aquatic organisms, particularly oysters. The aim of this study was to evaluate Acetylcholinesterase (AChE) activity and Micronucleus (MN) frequency in the oyster Crassostrea corteziensis in laboratory exposure with CPF (20, 40, 60, 80, and 160 µg/L) and in a field study. The results showed that AChE was reduced 60 - 82 % in oysters exposed to CPF, relative to the negative control. Similar AChE results were observed in oysters collected from the Boca de Camichín Estuary in Nayarit, Mexico; with respect to genetic damage, evaluated through MN, treatment with CPF did not induce the MN frequency, nor did the oyster from the field study exhibit an increase in this biomarker. These results suggest that C. corteziensis is a sensitive model for evaluating the acute toxicity of OP in laboratory studies as well in the field. In addition, it generates prospects on studying mechanisms through which the oyster could possess resistance to genotoxic agents, as well as its being a reliable model for evaluating the genotoxic effects of xenobiotics through the MN technique.